Предмет: Алгебра,
автор: sabinus1
5*(х-1)-3*(х+2)=-5х как это решить? помогите пж это решить
Ответы
Автор ответа:
2
5*(х-1)-3*(х+2)=-5х
5х-5-3х-6=-5х
5х-3х+5х=6+5
7х=11
х=11/7
х=1 4/7
5х-5-3х-6=-5х
5х-3х+5х=6+5
7х=11
х=11/7
х=1 4/7
sabinus1:
спасибо вам большое!)))0
Автор ответа:
1
5х-5-3х-6=-5х
2х-11=-5х
2х+5х=11
7х=11
х=1 4
--
7
2х-11=-5х
2х+5х=11
7х=11
х=1 4
--
7
Похожие вопросы
Предмет: Русский язык,
автор: nastiklastik720
Предмет: Математика,
автор: Аноним
Предмет: Геометрия,
автор: frost9359
Предмет: Математика,
автор: лена071